ANALISIS PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN MOBIL MEREK SUZUKI DI KOTA SEMARANG - Bambang Heriawan; Nanang Ari Utomo (ITB AAS Indonesia Surakarta, 2026)
The intense competition between car brands encourages companies to implement brand management strategies to create value and equity that can bind consumers. This study aims to determine the influence of brand equity elements consisting of brand awareness, brand association, perceived quality, and brand loyalty on consumer decisions to purchase Suzuki brand cars in the city of Semarang. This study used a quantitative descriptive method to describe the phenomenon that is the object of research on what it is and use statistical analysis to test the hypothesis. The population in this study are all consumers Suzuki car buyers in the city of Semarang. Samples taken as many as 100 people were taken to the consumers convenience sampling technique. Techniques of data collection using questionnaires. Analysis using multiple regression analysis, t test, F test, and test the coefficient of determination. Previous test the classical assumption of normality test, multicollinearity, and heteroscedasticity test. The results showed that: (1) brand awareness significantly influence the purchase decisions of Suzuki brand cars; (2) brand association significantly influence the purchase decision of the Suzuki brand cars. (3) perceived quality significantly influence the purchase decision of the Suzuki brand cars. (4) brand loyalty significantly influence the purchase decisions of Suzuki brand cars. This means that consumers who have a high loyalty to the Suzuki brand, it is certain that the consumers most likely to buy a Suzuki